Comparison of different lymphoma cell purging modalities: an experimental study with K422 lymphoma cells - Hundsdörfer, Patrick; Frühauf, Stefan; Haberkorn, M.; Höft, Raimund; Haas, Rainer; Zeller, W. Jens (Acta haematologica, 1999)
Blood-derived autografts from patients with non-Hodgkin’s lymphoma (NHL) are frequently contaminated with clonogenic lymphoma cells. In order to obtain a more efficient lymphoma cell depletion from the transplants we compared the efficiency of different purging techniques: B-cell-directed depletion, CD34+ selection by immunomagnetic beads (IMB selection) or by immunoadsorption with a biotin-avidin column (BAC selection). Furthermore, two combination approaches were investigated: IMB selection after B-cell depletion as well as BAC selection after B-cell depletion.